Public emotions and cognitions in response to ocean acidification. (15th April 2022) - Insinga, Maia L.; Needham, Mark D.; Swearingen, Thomas C.
Abstract: Ecological studies on ocean acidification (OA) are abundant, but there are only a few studies examining the human dimensions (social science) of this threat to marine environments. This article explored public emotions and cognitions (attitudes, norms) toward OA, and how these concepts are related to knowledge and risk perceptions associated with this threat. Data were from a survey of residents in the coastal and most populated regions of Oregon, USA ( n = 507). Respondents were grouped by their risk and knowledge, and shown four images depicting deteriorating conditions associated with OA, with questions measuring cognitions and emotions in response to each image. Knowledge about OA was quite low, and respondents perceived OA as a moderate risk to marine environments and a slight risk to themselves. As both knowledge and risk increased, awareness increased and emotions, attitudes, and norms became more negative, especially as conditions deteriorated. Implications and explanations of these findings were discussed. Highlights: This article examined cognitions and emotions regarding ocean acidification (OA). Data were from a survey of 507 residents in Oregon (USA). Knowledge about OA was low, and they perceived slight to moderate risks from OA. As knowledge and risk increased, emotions, attitudes, and norms were more negative. These cognitions and emotions became more negative as OA conditions deteriorated.